Observation of the equilibrium Cu B-CO complex and functional implications of the transient heme a 3 propionates in cytochrome ba 3-CO from Thermus thermophilus. Fourier transform infrared (FTIR) and time-resolved step-scan FTIR studies - Stavrakis, Stavros; Varotsis, Constantinos; Koutsoupakis, Constantinos (My University, 2002)
We report the first evidence for the existence of the equilibrium Cu B 1+-CO species of CO-bound reduced cytochrome ba 3 from Thermus thermophilus at room temperature. The frequency of the C-O stretching mode of Cu B 1+-CO is located at 2053 cm -1 and remains unchanged in H 2O/D 2O exchanges and, between pD 5.5 and 9.7, indicating that the chemical environment does not alter the protonation state of the Cu B histidine ligands. The data and conclusions reported here are in contrast to the changes in protonation state of Cu B-His-290, reported recently (Das, T. K., Tomson, F. K., Gennis, R. B., Gordon, M., and Rousseau, D. L. (2001) Biophys. J. 80, 2039-2045 and Das, T. P., Gomes, C. M., Teixeira, M., and Rousseau, D. L. (1999) Proc. Natl. Acad. Sci. U. S. A. 96, 9591-9596). The time-resolved step-scan FTIR difference spectra indicate that the rate of decay of the transient CU B 1+-CO complex is 34.5 s -1 and rebinding to heme a 3 occurs with k 2 = 28.6 s -1. The rate of decay of the transient Cu B 1+-CO complex displays a similar time constant as the absorption changes at 1694(+)/1706(-), attributed to perturbation of the heme a 3 propionates (COOH). The ν(C-O) of the transient Cu B 1+-CO species is the same as that of the equilibrium Cu B 1+-CO species and remains unchanged in the pD range 5.5-9.7 indicating that no structural change takes place at Cu B between these states. The implications of these results with respect to proton pathways in heme-copper oxidases are discussed
Keywords: Biochemistry; Ligands; Absorption; Copper compounds; Fourier transform infrared spectroscopy; Protons; Carbon; Histidine; Bacteria